Perancangan Sistem Informasi Pemeriksaan Barang Berbasis Web Menggunakan Metode SSAD - Falaah Abdussalaam; Badriansyah Badriansyah (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
The purpose of this study was to Analyze and Design an Information System of Goods Inspection at PT. Panasonic Gobel Indonesia Bandung. The problem is that the goods inspection administration system is still semi-manual so that the process of requesting and searching for goods inspection information is not optimal and prone to human error. Based on these problems, a Goods Inspection Information System was designed using the PHP programming language and MySQL database, while the system development process uses a Structured System Analysis and Design methodology (SSAD). The results of the research are Web-based Goods Inspection Information System according to company needs that can be accessed online and support information on goods inspection effectively and improve the quality of reporting in real-time.